Fachsprachliche Pluralität in der beruflichen Kommunikation - Roelcke, Thorsten (2022)
The modern working world is characterized by increasingly complex external and internal pluri- and multilingualism, which poses growing challenges for professional communication. In order to be able to systematically capture this increasing complexity, a separate model is required. In this model, on the one hand, the individual languages and their linguistic varieties of external and internal multilingualism and, on the other hand, the first-, second- and foreign-language competencies of individual persons are entered in a matrix. In this way, multilingual settings of professions or workplaces as well as multilingual profiles of individual persons can be described in a differentiated manner and corresponding political and didactic measures can be taken.
Keywords: Languages for Specific Purposes; professional communication; multilingualism; plurilingualism; language didactics